Developmental regulation of lifelong dental experiences and beliefs in Guangzhou and Hong Kong. (14th December 2018) - MacEntee, Michael I.; Wong, Sabrina T.; Chi, Iris; Lo, Edward C. M.; Minichiello, Victor; Soheilipour, Shimae; Mariño, Rodrigo
Abstract : Aims: The aim of this study was to explain through the life‐course and life‐span perspectives of developmental regulation theory the controls on dental experiences and beliefs throughout the lives of older people in Guangzhou and Hong Kong. Background: Dental diseases and disabilities among older people are serious public health concerns in China. Methods: A facilitator conducted eight focus groups, three in Hong Kong and five in Guangzhou, involving a total of 51 participants. She encouraged discussions about lifetime events to explain dental experiences and beliefs. Transcripts were coded and analysed using a constant comparative approach to identify themes that explained the regulators of dental experiences throughout the participants' lives. Results: Participants explained the influence of culture and history through critical events, and how external and internal factors regulated their current oral health status and beliefs. They emphasised the role of Traditional Chinese Medicine and family, and the stress of social upheaval compounded by a scarcity of dental services. They revealed also how current choice of dental services and health promotional programs, helped by personal food choice, self‐reliance, and scepticism, helped them to adjust and cope with dental diseases and disabilities and the commercialisation of dental services. Conclusions: Dental experiences and beliefs of older people living in Guangzhou and Hong Kong were regulated strongly during personal development by culture and history during critical events, and by various controlling factors, such as health promotion and choice of services supplemented by food choice, nutritional balance, self‐reliance, scepticism and social adjustments.